Materials for design - Lefteri, Chris, ....- (London : Laurence King Publishing, 2014)
Over the last 10 years there has been a huge growth in the area of materials and design, but most books on the subject deal with advanced, semi-formed materials (that is, materials sold as sheet, rod, tube, etc.). This new book provides much-needed information on the raw materials, and the 'low-down' on what these materials can be used for. The information provided in the book allows professional designers and students from a range of disciplines – but focusing on product design – to understand in simple, exciting, thought-provoking, visual terms different qualities and features of materials. The subject is presented from the perspective of design, and relevant case studies are used to inspire designers into new ways of thinking about materials. As well as standard and widely available materials, the book also contains emerging materials such as smart materials and self-healing plastics, offering a comprehensive guide to material selection for designers.
Includes bibliographical references (pages 246-248) and index.
Keywords: Raw materials; Smart materials in design; Product design; Sustainable design; Industrial design